Guide to build YOLO, a creativity-stimulating robot for children - Alves-Oliveira, P. (2019)
YOLO is a non-anthropomorphic social robot designed to stimulate creativity in children. This robot was envisioned to be used by children during free-play where they use the robot as a character for the stories they create. During play, YOLO makes use of creativity techniques that promote the creation of new story-lines. Therefore, the robot serves as a tool that has the potential to stimulate creativity in children during the interaction. Particularly, YOLO can stimulate divergent and convergent thinking for story creations. Additionally, YOLO can have different personalities, providing it with socially intelligent and engaging behaviors. This work provides open-source and open-access of YOLO's hardware. The design of the robot was guided by psychological theories and models on creativity, design research including user-centered design practices with children, and informed by expert working in the field of creativity. Specifically, we relied on established theories of personality to inform the social behavior of the robot, and on theories of creativity to design creativity stimulating behaviors. Our design decisions were then based on design fieldwork with children. The end product is a robot that communicates using non-verbal expressive modalities (lights and movements) equipped with sensors that detect the playful behaviors of children. YOLO has the potential to be used as a research tool for academic studies, and as a toy for the community to engage in personal fabrication. The overall bene t of this proposed hardware is that it is open-source, less expensive than existing ones, and one that children can build by themselves under expert supervision.